Causal effect of gut microbiota on Gastroduodenal ulcer: a two-sample Mendelian randomization study - Zhang, Jing; Hu, Yingqiu; Wu, Lidong; Zeng, Qi; Hu, Bin; Luo, Zhiqiang; Wang, Yibing (Frontiers in Cellular and Infection Microbiology, 2023)
Background Gastroduodenal ulcers are associated with Helicobacter pylori infection and the use of nonsteroidal anti-inflammatory drugs (NSAIDs). However, the causal relationship between gastroduodenal ulcers and gut microbiota, especially specific gut microbiota, remains unclear. Methods We conducted an analysis of published data on the gut microbiota and Gastroduodenal ulcer using genome-wide association studies (GWAS). Two-sample Mendelian randomization (MR) analysis was performed to determine the causal relationship between gut microbiota and Gastroduodenal ulcer. Sensitivity, heterogeneity, and pleiotropy analyses were conducted to confirm the accuracy of the research findings. Results Our study showed that the abundance of Enterobacteriaceae, Butyricicoccus, Candidatus Soleaferrea, Lachnospiraceae NC2004 group, Peptococcus, and Enterobacteriales was negatively correlated with the risk of Gastroduodenal ulcer. Conversely, the abundance of Streptococcaceae, Lachnospiraceae UCG010, Marvinbryantia, Roseburia, Streptococcus, Mollicutes RF9, and NB1n was positively correlated with the risk of Gastroduodenal ulcer. MR analysis revealed causal relationships between 13 bacterial genera and Gastroduodenal ulcer. Conclusion This study represents a groundbreaking endeavor by furnishing preliminary evidence regarding the potentially advantageous or detrimental causal link between the gut microbiota and Gastroduodenal ulcer, employing Mendelian Randomization (MR) analysis for the first time. These discoveries have the potential to yield fresh perspectives on the prevention and therapeutic approaches concerning Gastroduodenal ulcer, with a specific focus on the modulation of the gut microbiota.